Predictive factors for technically difficult endoscopic submucosal dissection in large colorectal tumors - He, Yuqi; Wang, Xin; Du, Yongqiang; Yee-Wa Yung, Victoria; Jin, Peng; Sheng, Jianqiu (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Endoscopic submucosal dissection (ESD) for colorectal tumors is dangerous, particularly those that are large. However, the technical difficulty in resecting large tumors in the colonrectum has seldom been investigated. Materials and Methods: Between October 2012 and January 2015, 36 consecutive large colorectal tumors were resected by ESD at the endoscopic center of PLA Army General Hospital. Five factors were investigated in predicting the technical difficulty in resecting such tumors. Results: En bloc resection, complete (R0) resection, and curative resection rates were 83.33% (30/36), 80.56% (29/36), and 77.78% (28/36), respectively. Tumor location in a flexure was risk a factor for difficult ESD in the colonrectum as measured by perforation (4.55, 0.09–6.25), non-en bloc resection (4.94, 0.10, 9.45), and dissection speed (β±SE: 1.75±0.05). When tumor size increased, the perforation rate also increased (9.93, 0.96–10.32). Conclusion: ESD was more technically demanding in flexures for resecting large colorectal tumors, and for large tumor effective technique to close perforation is essential. Our study will guide endoscopists in using ESD to remove large colorectal tumors.